The impact of final demand on energy sectors' interregional output - Ernawati, Ernawati; Natsir, Muhammad; Asri, Mansyur (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study investigates the influence of aggregate demand on the interregional energy sector in Indonesia, aiming to ascertain whether the proximity of regions impacts the demand within the energy sector. Utilizing data from the Input-Output Indonesia Interregional Table, this research encompasses six regions: Sumatra, Java, Bali & Nusa Tenggara, Kalimantan, Sulawesi, and Maluku & Papua. The energy sectors analyzed include oil, gas & geothermal mining, coal & lignite mining, coal industry & oil, gas refinery, and electricity and gas procurement & ice production. Findings indicate that the electricity sector exhibits relatively high sensitivity and dispersion power indices, whereas the gas procurement & ice production sectors display low sensitivity and dispersion power indices. Exports are identified as the primary contributors to the Oil, Gas, & Geothermal Mining and Coal & Lignite Mining sectors. Conversely, household consumption has the most significant impact on the other sectors. Crucially, the study reveals that the effect of a region's final demand on the output of another region is not directly correlated with geographical proximity. This insight leads to the recommendation that energy supply procurement policies should consider other regions' demands and economic developments, particularly those substantially influencing output enhancement.